Revolusi Desain Sistem Berbasis AI Generatif dalam Transformasi Kreativitas dan Inovasi Teknologi Modern - Muhammad Rinov Cuhanazriansyah; Edy Sutanto; Karin Setia Ningrum; Engga Alwi Shihab Alzubair (Jurnal Pendidikan Teknologi Informasi dan Vokasional, 2025)
This study aims to descriptively examine the influence of generative Artificial Intelligence (AI) on efficiency and creativity in system design in Indonesia, as well as its implications for the field of Computer Architecture and Organization (CAO). A qualitative descriptive method was employed, using data sources from 16 recent journals and scientific publications discussing the application of generative AI in various fields such as graphic design, product design, digital education, and information systems. The results of the study indicate that the implementation of generative AI has a significant positive impact on design processes and technological learning. On average, time efficiency increased by 56.3%, while creativity improved by 47.8%. This technology not only accelerates production processes and idea exploration but also strengthens collaboration between humans and machines in creating innovative works. In the context of CAO education, generative AI helps students understand computer system concepts through adaptive simulations and interactive visualizations, making learning more dynamic and applicable. However, the study also identifies ethical challenges and copyright issues that require serious attention. Therefore, digital literacy, regulation, and ethical policies are needed to ensure responsible use of AI. Overall, this research concludes that generative AI serves as a key catalyst for transforming design and technological learning in Indonesia, with great potential to enhance efficiency, creativity, and innovation quality in the modern digital era.Kata kunci: Artificial Intelligence, AI Generatif, Desain Sistem,  Efisiensi, Kreativitas, Arsitektur dan Organisasi Komputer